Post-Less Hip Arthroscopy With Positioning in Lateral Decubitus - Jacob D. Kodra, B.S.; Christopher Papatheofanis, M.S.; Robert Healey, M.B.A.; Michael P. Muldoon, M.D. (Arthroscopy Techniques)
The number of pathologies treated successfully by hip arthroscopy continues to increase, and multiple efficacious techniques exist to perform this procedure. Hip arthroscopy performed with patients in the lateral decubitus position without a perineal post is less appreciated yet encourages increased visualization of the hip joint, improved ergonomics and maneuverability, and decreased postoperative complications. This article includes a detailed description of post-less hip arthroscopy with patient positioning in lateral decubitus.